Cationic BODIPY Photosensitizers for Mitochondrion-Targeted Fluorescence Cell-Imaging and Photodynamic Therapy - Isabel Wen Badon; Jun-Pil Jee; Temmy Pegarro Vales; Chanwoo Kim; Seungbin Lee; Jaesung Yang; Si Kyung Yang; Ho-Joong Kim (Pharmaceutics, 2023)
The straightforward synthesis of three cationic boron-dipyrromethene (BODIPY) derivatives and their mitochondria-targeting and photodynamic therapeutic (PDT) capabilities are reported. Two cancer cell lines (HeLa and MCF-7) were used to investigate the PDT activity of the dyes. Compared to their non-halogenated counterparts, halogenated BODIPY dyes exhibit lower fluorescence quantum yields and enable the efficient production of singlet oxygen species. Following LED light irradiation at 520 nm, the synthesized dyes displayed good PDT capabilities against the treated cancer cell lines, with low cytotoxicity in the dark. In addition, functionalization of the BODIPY backbone with a cationic ammonium moiety enhanced the hydrophilicity of the synthesized dyes and, consequently, their uptake by the cells. The results presented here collectively demonstrate the potential of cationic BODIPY-based dyes as therapeutic drugs for anticancer photodynamic therapy.